Achievement goal orientations, sport motivation and competitive performance in beach volleyball players - Knoblochova, M.; Mudrak, J.; Slepicka, P. (Acta Gymnica, 2021)
Background: From the perspective of achievement goal orientation theory, athletes may evaluate their performance by comparing current achievements with previous achievements (task orientation) or with those of other athletes (ego orientation); these two orientations may affect their sport motivation and performance outcomes in different ways.